Revised taxonomic status of Eidophasia zukowskyi Amsel, 1938 (Lepidoptera, Plutellidae) with first description of its male and female genitalia - Baraniak, Edward; Sohn, Jae-Cheon (Zootaxa, 2016)
We revise the taxonomic status of Eidophasia zukowskyi Amsel, 1938, and we provide the first descriptions of the genitalia of both sexes. A diagnostic summary is given with illustrations for a similar congener, Eidophasia syenitella (Herrich-Schäffer, [1854]).